Transformasi Inovasi Perencanaan Pendidikan Islam di Era Digital: Kajian Konseptual terhadap Adaptasi Manajemen Pendidikan Berbasis Teknologi - Ardian; Ahmad Salabi; Yahya Mof (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Digital technology development has brought fundamental changes to various aspects of life, including educational management. Digital transformation not only affects learning processes but also requires a paradigm shift in educational planning, which serves as a core function of educational management. In the context of Islamic education, planning innovation has become a strategic necessity to address the challenges of globalization, technological advancement, and twenty-first-century competencies while maintaining Islamic values. This study aims to analyze innovations in Islamic educational planning in the digital era, identify implementation challenges, and explain strategies for strengthening educational planning that is adaptive to technological developments. This research employed a qualitative approach using a library research method. Data were collected from books, scientific journal articles, regulations, and relevant academic documents, which were then analyzed using content analysis techniques. The findings indicate that innovations in Islamic educational planning are characterized by the utilization of educational management information systems, data-driven decision-making, digitalized institutional governance, and the integration of digital competencies with Islamic values. However, the implementation of digital transformation still faces several challenges, including limited technological infrastructure, low digital literacy among human resources, and resistance to change. Therefore, strengthening digital capacity, fostering an innovative organizational culture, and developing visionary leadership are essential to establishing an effective, adaptive, and sustainable Islamic educational planning system.